Immunological Susceptibility of Metropolis Population to Measles in its Elimination Stage - A. V. Nozdracheva; M. N. Asatryan; M. N. Asatryan; I. S. Shmyr; I. F. Ershov; D. V. Solov’ev; V. M. Glinenko; S. N. Kuzin (Эпидемиология и вакцинопрофилактика, 2019)
Relevance. In the context of high coverage of the population with preventive measles vaccination (more than 90% according to official statistics), in recent years there has been a complication of the epidemic situation for this infection, which necessitates an in-depth study of the causes and factors that contributed to the increase in morbidity. The aim of the study was to assess the susceptibility of the population of Moscow to measles on the basis of preventive vaccinations coverage data in a planned immunization and on epidemic indications. Materials and methods. To achieve this goal, epidemiological, statistical methods and Geographic Information System (GIS) technologies were used; the electronic database of materials of sanitary and epidemiological investigation in measles foci was created. Results. Тhe practical applicability of the proposed approach was shown, risk groups for measles incidence were identified. Due to the low coverage of routine preventive vaccinations and epidemic indications (compared with official statistics), the most vulnerable to measles are the age groups from one to two years and from three to six years, where these indicators were the lowest among the total population surveyed (routine and epidemic indications: about 55.9%, 10.8% and 75.3%, 40% respectively). Among the adult population, a decrease in the coverage of preventive vaccinations was revealed as the age of contact persons increased from 81.3% in the age group 20–35 to 51.0% in the age group 36 years and older. With the help of GIS technology, the possibility of visualization of the disease spread in a specific period of time in a certain area of the observed city was shown. Conclusions. According to the results the situation with measles in Moscow remains tense. There is a need for correction of the population immunization with the aim of increasing vaccination coverage in the individual age groups, and correction of statistical accounting of the facts of vaccination.